VD_FINDINFO Jug / 2020 / 273 vom 27. November 2019 - VD Tribunal cantonal (2019)
DÉCISION D'IRRECEVABILITÉ, RÉSILIATION IMMÉDIATE, HARCÈLEMENT PSYCHOLOGIQUE | 61 LPers-VD, 59 CPC (CH), 60 CPC (CH), 66 CPC (CH)